2018
DOI: 10.1158/1541-7786.mcr-17-0767
|View full text |Cite
|
Sign up to set email alerts
|

TRPM7 Regulates AKT/FOXO1–Dependent Tumor Growth and Is an Independent Prognostic Indicator in Renal Cell Carcinoma

Abstract: Transient receptor potential melastatin 7 (TRPM7) is important for the tumorigenesis and progression of several cancers. However, little is known about TRPM7 expression and its clinical significance in clear cell renal cell carcinoma (ccRCC). The expression dynamics of TRPM7 was examined in a clinical cohort of RCC specimens by qPCR, immunoblotting, and IHC staining. A series of and assays were performed to elucidate the function of TRPM7 in RCC and the underlying mechanisms. For the first time, results demons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…In the present study, TRPM7 was identified as the target gene of miR‐9‐5p via luciferase assay. Accumulating evidence indicates that TRPM7 is essential for multiple cellular processes, including survival, proliferation and migration in stem cells and endothelial cells via PI3K/Akt pathways . It has been well demonstrated that TRPM7 could inhibit the growth and migration of human umbilical vein endothelial cells (HUVECs) .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, TRPM7 was identified as the target gene of miR‐9‐5p via luciferase assay. Accumulating evidence indicates that TRPM7 is essential for multiple cellular processes, including survival, proliferation and migration in stem cells and endothelial cells via PI3K/Akt pathways . It has been well demonstrated that TRPM7 could inhibit the growth and migration of human umbilical vein endothelial cells (HUVECs) .…”
Section: Discussionmentioning
confidence: 99%
“…The tumor suppressor and anti-metastatic functions of the hypermethylated MIR-129-2 gene we discovered (Beresneva et al, 2013), are consistent with the data that miR-129-3p downregulates multiple metastasis-related genes in RCC cells, including SOX4 , and also decreased phosphorylation of focal adhesion kinase and expression of MMP-2/9 (Chen et al, 2014). In addition, miR-129-3p is involved in miR-129-3p/TRPM7/AKT/FOXO1 signaling pathway (Zhao Z. et al, 2018). The collective data confirm the ability of miR-129-3p to restrain metastasis in ccRCC.…”
Section: Aberrantly Methylated Mirna Genes In Ccrccmentioning
confidence: 99%
“…The expression of TRPM7 in GC was assessed using the IHC scoring method confirmed in previous studies [ 23 , 24 ]. During evaluation process, cytoplasmic and membranous staining in tumor cells were taken into consideration.…”
Section: Methodsmentioning
confidence: 99%